Weston Langford Railway Photography : Documenting railways and related infrastructure since 1960. - Langford, Weston; Godfrey, Andrew ([Australia]: Weston Langford.)
"As a railway enthusiast Weston was a member of a privileged generation. Many of the things we once took for granted simply are not there any more. The special train programme is a shadow of its former self. Photographic stops are deemed to be too dangerous. The free access to many places of railway interest is now effectively closed off. It remains now to share the good things that came Weston's way." "This website was built by Weston's son-in-law, Andrew Godfrey, who continues to maintain the site."
Title from title screen (viewed on 16 February 2018)
Mode of access: Available Online. Address as at 27/03/2018
Selected for archiving
Keywords: Langford, Weston; Photography of railroads -- Australia; Railroad trains -- Australia -- Photographs; Australian